Knowledge, Attitude, and Practice of Physiotherapists in COVID-19 ICUs: A National Survey - Nikitha Suresh Babu; Vijay Pratap Singh; K. Shyam Krishnan; Dattatray Prabhu (The Scientific World Journal, 2024)
Background. COVID-19 belongs to the beta-corona cluster that spreads enormously via aerosols. Physiotherapists must be knowledgeable about the symptoms, mode of transmission, risk mitigation strategies, and practice guidelines for COVID-19. Objective. This study aimed to assess physiotherapists’ knowledge of COVID-19 guidelines, their attitude toward this new evolving field, and their practice routines in India’s COVID-19 ICUs. Methods. It was a cross-sectional study. A total of 600 questionnaires were distributed through e-mail and WhatsApp to physiotherapists using Google Forms between February 2022 and January 2023. The questionnaires consisted of demographics and 23 questions in three sections about the knowledge, attitude, and practice of physiotherapists working in the COVID-19 ICU. Data analysis was carried out using Jamovi. Results. A total of 136 responses were obtained from 18 states of India. Of 136 participants, 89 were female (65.4%) and 47 were male (34.6%). The highest level of qualification was BPT (n = 69 (50.7%)), followed by MPT (n = 62 (45.6%)) and Ph.D. (3 (3.7%)). The knowledge about COVID-19 guidelines is fair. Only 21.3% of the physiotherapists received training before being deployed in COVID-19 ICUs, and the CARP protocol was well known by only as few as 10.3%. The criteria advised for close monitoring of patients during treatment was aware by 29.4%. Most physiotherapists have a good attitude toward treating COVID-19 patients; 70.63% strongly agree that physiotherapy is vital in these patients despite the risk of self-exposure, and 64.7% agree that physiotherapy should be initiated during all phases of COVID-19. Physiotherapists follow good practices for COVID-19 patients in the ICU, which is as per the guideline recommendation. Conclusion. Physiotherapists working in COVID-19 ICUs have a fair knowledge of the existing physiotherapy guidelines for COVID-19, and they exhibit good attitudes and practice patterns.